HOMO–LUMO coupling: the fourth rule for highly effective molecular rectifiers. Issue 24 (12th June 2017) - Thong, Aaron Zhenghui; Shaffer, Milo S. P.; Horsfield, Andrew P.
Abstract : Charge transport simulations of 4-thiophenylazafulleroid have shown that it has good rectifying character due to a HOMO–LUMO pinning effect. Abstract : Three rules for creating highly effective unimolecular rectifiers that utilize asymmetric anchoring groups have been proposed by Van Dyck and Ratner [Ratner et al., Nano Lett., 2015, 15, 1577–1584]. This study investigates their proposed rectification mechanism in a functionalised azafullerene system (4TPA–C60 ) and identifies a fourth rule. NEGF-DFT shows that 4TPA–C60 fulfills the three design rules and finds that a saturated bridge is not required to fulfil the third rule, contrary to previous belief. Instead a twisted-π bridge decouples the donor and acceptor states whilst still providing a high conductance pathway. The molecular junction has a calculated rectification ratio of 145 at a bias of ±1 V and the U-type rectification mechanism is driven by the pinning of the HOMO to the LUMO when the device is forward biased, but not when reverse biased. The switching behaviour is a result of a charge dipole forming at different interfaces for different bias directions. An additional design rule is thus proposed: charge transport should allow bias dependent coupling of filled to unfilled states. The findings in this work not only help in understanding charge transport in molecular rectifiers, but also have wider implications for the design of molecular resonant tunneling devices.